'lips move, uttering inaudibly': The Female Voice in Samuel Beckett's …but the clouds …. Issue 2 (September 2020) - Vashisht, Jivitesh
Abstract : While the dialogue between Samuel Beckett's …but the clouds… and W. B. Yeats's 'The Tower' has been thoroughly examined, much less attention has been paid to the female voice that inaudibly recites the poetic fragment in what constitutes the teleplay's chief intertextual gesture towards Yeats's poem. Aligning this oversight with the more pervasive disregard within Beckett Studies to the gendered specificity of Beckett's voices, this essay elaborates the absent presence of the female voice in the teleplay – crystallised in the image of W's silently moving lips – from the interlocking perspectives of intertextuality, technology, and spectatorship. It draws attention to Beckett's sustained preoccupation with the female voice during the composition process, as well as the intertextual and technological operations through which he orchestrates its paradoxical status. Even though as a speech-deprived female body functions as the locus of these overlapping processes, I argue that … but the clouds… ultimately subverts associations of the feminine with discursive inadequacy and bodily impairment; if anything, Beckett here attributes deficiency and incompletion to male subjectivity and the televisual medium.